Stock Price Analysis in Healthcare Sector Companies On the Indonesia Stock Exchange (International Journal of Scientific Research and Management (IJSRM), 2025)
This study analyzes the influence of profitability, liquidity, and solvency on stock prices with dividend policy as a mediator variable in healthcare sector companies listed on the Indonesia Stock Exchange for the 2020-2023 period. Using a quantitative approach with a comparative causal design, this study involved 9 healthcare companies selected through purposive sampling, resulting in 36 observations. Profitability is measured using Return on Assets (ROA), liquidity using Cash Ratio, solvency using Equity to Assets Ratio, and dividend policy using Dividend Payout Ratio. Data analysis uses Moderated Regression Analysis (MRA) after meeting the classical assumption test. The results of the study show that profitability has a negative effect on stock prices (β=-4,236,647; p=0.026). Liquidity showed a positive but insignificant effect (p=0.075), while solvency had a significant positive effect (p=0.023) on stock valuation. The dividend policy has been proven to moderate the relationship between profitability and stock price positively (p=0.033), not moderate the relationship between liquidity and stock price (p=0.119), but to moderate the negative relationship between solvency and stock price (p=0.017). The research model showed superior predictive ability with an adjusted R-square of 0.750, indicating that 75% of stock price variations could be explained by the variables in the model. These findings make a theoretical contribution to understanding the dynamics of the healthcare sector capital market and the strategic implications for management in the formulation of optimal financial policies.